(3GdejSQ GdLdjd Ydi eNJUQ Ndjds - (3eMfU HGH Hf CYHjO GdOjeGfis; (3Ndjd GHf ESMb GdLfOj GdeGdcj,J (B767 (3g` s ((3ehQJjGfjG s)
(3ChdgG (B:s
(3jHOC HcJGH GdHjY Hbhdg HSe Gddg GdQMef GdQMje cJGH ai GdHjY hgh eG jfHZi GdEYJfGA Hg dYehe GdHdhi Hg hbhd HYVge EPdkG jNdh ecda ZGdHkG ef HjY Ch TQGA s
(3BNQgG (B:s
(3adGMX HNdGa GdNdGa GdELGQI HfbO Ydi Sbi MGFW ReffkG aCZfi Yfg GdeWQai hGdeSGaGJ Ydi GdeSGeMI hGddg JYGdi CYde HGdUhGH gPG BNQ eG jSQ Gddg ef GdcdGe Ydi gPG GdLRA s
(3HgG fXGe GdJYbjHIs
(3fSNI eYfhfI HGdMHQ GdCMeQ hYdjgG JUMjMGJs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs